The Political Economy of Governance: Institutions, Political Performance and Elections - Schofield, Norman (Springer, 2015)
Understanding the governance of nations is a key challenge in contemporaneous political economy. This book provides new advances and the latest research in the field of political economy, dealing with the study of institutions, governance, democracy and elections. The volume focuses on issues such as the role of institutions and political governance in society, the working of democracy and the electoral performance in several case studies. The chapters involve cutting edge research on many different countries, including the USA, Great Britain, Germany, Spain and the Third World. The authors of the chapters are leading scholars in political economy from America, Europe and Asia.